Vladimir Mironov’s metaphysics and university education transformation - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2021)
The article deals with the specificity of philosophical knowledge, metaphysics as its semantic core and the problems of transforming modern humanitarian university education, which was developed in the work of Vladimir Mironov. V. V. Mironov is a well-known Russian scientist, doctor of philosophy, professor, corresponding member of the Russian Academy of Sciences, dean of the faculty of philosophy of the Lomonosov Moscow State University. The author analyses current problems related to the role of philosophy in shaping the image of the future in modern culture, reforming university education, the consequences of introducing scientometric methods into the educational process, the readiness of higher education responding to the challenges of the times, global instability, commercialisation, digitalisation, etc. The scientific position of V. V. Mironov on topical problems of transforming modern society, its assessment and reflections on the prospects for teaching philosophy and the humanities.